A Neoconservative Theory of International Politics? - Mahabir, Lakshana (Université d'Ottawa / University of Ottawa, 2018)
Neoconservatism has long had a tenuous relationship with International Relations theory. Despite an abundance of explanatory material and its influence in US foreign policy, few works in IR have attempted to build a stand-alone theory out of it. Furthermore, previous work on the topic has resulted in an under-developed and poor understanding of the movement’s core ideas. The thesis redefines neoconservatism as a trifecta of i) a set of explanatory ideas on world politics, ii) an approach to foreign policy, and iii) an ideology that stems from the European Enlightenment, all the way to the present day. Using this expanded conceptualization, the thesis builds a theory out of what can broadly be considered an ideology. The theory takes the form of an ideal-type construct and emphasizes hegemony in the international system. It offers an explanation for the causes of alliances, as well as regional and systemic conflicts. The theory also adopts a prescriptive function and offers an account of foreign policy analysis. It is highly recommended that the assumptions of the theory that are laid out here be tested in future work.
Keywords: neoconservatism; international relations; neo-conservatism; international relations theory; US foreign policy; ideology; theory of international politics; hegemony; liberalism; conservatism; Leo Strauss; Edmund Burke; Allan Bloom; Irving Kristol; Bill Kristol; Robert Kagan; Paul Wolfowitz; Jeane Kirkpatrick; Bret Stephens; Daniel Patrick Moynahan